Aggregation States and Segmental Dynamics of Poly(methyl methacrylate) in Nanofiber Mats - Kawahara, Keigo (Langmuir : the ACS journal of surfaces and colloids, 2023)
Nanofiber mats composed of polymers, having a large surface-to-volume ratio and high porosity, have been widely applied in the environmental and biomedical fields but fundamental knowledge on the polymer chains in the mats seems to be limited. We here report the aggregation states and segmental dynamics of poly(methyl methacrylate)s (PMMAs) with different stereoregularities in electrospun nanofiber mats. Attenuated total reflectance Fourier transform infrared (ATR/FTIR) spectroscopy revealed that, in the case of atactic PMMA (at-PMMA), the population of the trans-trans conformation of the main chain part, which allows carbonyl groups of the side group to interact affirmatively with each other, increased in the electrospun nanofiber mat. On the other hand, in the case of isotactic PMMA (it-PMMA), the skeletal conformation was unchanged even in the nanofiber mat. As a result of the aggregation states of PMMA chains, the glass-transition temperature (Tg) of the electrospun nanofiber mats increased and remained unchanged from the corresponding bulk value for at- and it-PMMA, respectively. These findings should be useful for designing materials and devices composed of electrospun nanofibers